Occasional Tillage and Nitrogen Application Effects on Winter Wheat and Grain Sorghum Yield - A. K. Obour; J. D. Holman; A. J. Schlegel (Kansas Agricultural Experiment Station Research Reports, 2019)
Occasional tillage ahead of winter wheat planting could alleviate herbicide-resistant weeds, redistribute soil acidification, and improve seedbed at wheat planting. The objective of this study is to determine occasional tillage and nitrogen (N) fertilizer application effects on winter wheat, and grain sorghum yields and soil quality in a wheat-sorghum-fallow cropping system. Treatments were three tillage practices: 1) continuous no-tillage (NT); 2) continuous reduced-tillage (RT); and 3) single tillage operation every 3 years (June-July) ahead of winter wheat planting [occasional tillage (OT)]. The sub-plot treatments were assigned to four N fertilizer rates (0, 40, 80 and 120 lb/a of N). Preliminary results showed tillage had no effect on winter wheat grain yield. Applying N fertilizer increased wheat yield, ranging from 21 bu/a with no N fertilizer to 29 bu/a when N fertilizer was applied at 120 lb/a of N. Tillage and N fertilizer effects on grain sorghum yield varied over the 2 years of the study. Grain sorghum yields in 2017 decreased with RT but tillage had no effect on sorghum yields in 2018. Averaged across tillage and years, sorghum grain yield was 54 bu/a with no N fertilizer and 84 bu/a when N was applied at 120 lb/a of N. Both sorghum and winter wheat grain yields obtained with 80 lb/a of N were not different from those with 120 lb/a of N, suggesting 80 lb/a of N may be adequate for both crops.
Keywords: nitrogen; occasional tillage; winter wheat